2007
DOI: 10.1111/j.1365-2486.2007.01521.x
|View full text |Cite
|
Sign up to set email alerts
|

Simulated climate change provokes rapid genetic change in the Mediterranean shrub Fumana thymifolia

Abstract: Rapid climate change will impose strong directional selection pressures on natural plant populations. Climate-linked genetic variation in natural populations indicates that an evolutionary response is possible. We investigated such a response by comparing individuals subjected to elevated drought and warming treatments with individuals establishing in an unmanipulated climate within the same population. We report that reduction in seedling establishment in response to climate manipulations is nonrandom and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 51 publications
1
80
1
3
Order By: Relevance
“…Similar local population differentiation in Fumana thymifolia (Jump et al 2009) may have enabled this species to undergo rapid genetic change in response to experimental drought and temperature manipulations (Jump et al 2008). If true, it suggests that fine-scale substrate heterogeneity is of profound significance for the response of grassland communities to climate change, as Fridley et al (2011) further showed that many species in this system respond to changes in microsite water availability and temperature by shifting their abundance along the soil depth gradient.…”
Section: F U N C T I O N a L V A R I A T I O N W I T H R E S P E C T mentioning
confidence: 88%
See 1 more Smart Citation
“…Similar local population differentiation in Fumana thymifolia (Jump et al 2009) may have enabled this species to undergo rapid genetic change in response to experimental drought and temperature manipulations (Jump et al 2008). If true, it suggests that fine-scale substrate heterogeneity is of profound significance for the response of grassland communities to climate change, as Fridley et al (2011) further showed that many species in this system respond to changes in microsite water availability and temperature by shifting their abundance along the soil depth gradient.…”
Section: F U N C T I O N a L V A R I A T I O N W I T H R E S P E C T mentioning
confidence: 88%
“…Moisture stress is considered to be the primary driver of fine-scale adaptive differentiation in several conifer species (Jump & Peñuelas 2005), and drought has led to the rapid evolution of drought avoidance strategy in the annual plant Brassica rapa (Franks 2011). Further, significant local (<500 m 2 ) population differentiation has been reported in Fumana thymifolia (Jump et al 2009), which may have contributed to the ability of this species to undergo rapid genetic change following 5 years of experimental drought and temperature manipulations (Jump et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Climate manipulation experiments have demonstrated that some plant populations may be able to adapt to higher temperatures (Jump et al 2008), although whether this is sufficient to ensure population survival is unknown. Adaptive capacity is likely to be low in unique and isolated locations such as in the Stirling Range (Pittock 2003).While gene flow will aid adaptation to warming climates in relatively contiguous populations, for isolated populations this would be more limited and may lead to reduced levels of climate-related genetic variation rendering them less able to adapt to any further changes (Jump & Peñuelas 2005).…”
Section: Geographic Range and Germination Nichementioning
confidence: 99%
“…Various techniques of molecular biology have been applied to natural forest populations. Field studies of altitudinal gradients in the Montseny Mountains [27][28][29] and field experiments with warming and drought manipulation in the Garraf Mountains in typical Mediterranean shrubland [30] have demonstrated that species acclimate and adapt (evolve) quickly to climate change. The frequency of alleles of genes associated with these responses to the climate have been quantified in populations, and the role of epigenetic modifications in a fast-adaptive response has been determined.…”
Section: Responses At the Molecular Level And In The Use Of Chemical mentioning
confidence: 99%